KELAYAKAN FILM DOKUMENTER DALAM SUBMATERI PENCEMARAN AIR KELAS X SMA - Wiwin, Mardonius Muliadi; Hardigaluh, Basuki; Candramila, Wolly (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to determine the feasibility of documentary film on the Water Pollution Submaterial. The research used quantitative descriptive method. Success in the learning process become increasingly important considering that the water pollution did not only affect the life of water biota, but also poisoned the source of drinking water and animal food, as well as imbalancing the river ecosystem. With regards to environmental pollution material, the documentary medium could also provide direct and indirect motivation in daily life so that students were expected to understand and could implement the importance of keeping the environment healthy. The results of the documentary film validation containing the result of water quality analysis on Water Pollution Submaterial obtained average total validation of 3.05 (valid) for the material aspects and 3.21 (valid) for the medium aspects, but still needed to be repaired before its use on the learning of Water Pollution Submaterial for first grade students of senior high school.Â Keywords: Documentary Film, Submaterial Water Pollution